Prediction of entrepreneurship : an ordered regression approach - Silva, Francisco (2018)
Entrepreneurship is a popular research topic over the last several decades. Various authors study the characteristics that best define future entrepreneur profiles. In this paper, we apply a framework to screen school populations in the Azores Islands, Portugal, for prospects of entrepreneurship and to study the profiles of those who show noticeably entrepreneurial orientations. The contribution of the paper consists of applying ordered regression to explain the entrepreneurial prospects of students in high school.